GESTÃO SOCIAL: FERNAND BRAUDEL E A AMPLIAÇÃO DOS DEBATES EM TORNO DE SUA CONTEXTUALIZAÇÃO HISTÓRICA - Miguel Pacifico Filho (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2018)
We aim to demonstrate that the criticism directed to Social Management (SM)are built on historical bases capable of debates and extension of theoretical frameworks.We will expose the discussions that, held between critics and proponents of the idea of consolidation of SM as a field of knowledge, are based on classical authors such as Adorno, Karl Popper and Boa Ventura de Souza Santos and develop since the ‘90s, which confers them density and historicity. We will demonstrate the possibility of opening debates starting from criticism built about popular participation throughout the history of Brazil, and inserting another form of perception of the historical processes that make up the formation of a field of knowledge. We use the concept of long term proposed by Fernand Braudel, through which it is possible to understand that the historical facts, among them the establishment of an area of knowledge, should be observed from the plurality of their times, that can be structural, cyclical or factual. We conclude, from the comparative analytical perspective with another field of knowledge, history, that the Social Management is an area of knowledge and as such is in the process of discussion of its assumptions and paradigms.